Effect of dietary fat on the activity of palmitic acid elongase in the blood serum and liver of rats - Velichko, V. (Journal of Education, Health and Sport, 2022)
Background. To determine the effect of dietary fats on the activity of palmitic acid elongase by two methods, using indicators of the fatty acid composition of lipids in the blood serum and liver of rats. Methods. Edible vegetable oils were used: high linoleic (HLSO) and high oleic (HOSO) sunflower oils, palm oil (PO). Fats were introduced into the fat-free diet (FFD) in the amount of 5 % instead of the same amount of starch. The animals were fed for 30 days. A fraction of neutral lipids (triglycerides + cholesterol esters) was isolated from blood serum and liver, and the fatty acid composition was determined in it by gas chromatography. Results. HLSO consumption reduced the biosynthesis of energy fatty acids (C16:0, C16:1, C18:0 and C18:1) in the neutral fraction of serum and liver lipids. A new method for assessing the level of palmitic acid elongase, taking into account the metabolism of palmitic and stearic acids, is proposed, which gives higher values than the commonly used method for assessing elongase. With the help of the new method, elongase activation when HOSO is consumed was determined. Conclusions. A new method is proposed for the determination of palmitic acid elongase, which takes into account the metabolism of fatty acids. It has been established that the consumption of HLSO reduces the biosynthesis of energy fatty acids. Consumption of HOSO increases elongase activity.